The Effect of Worked-Examples on Students’ Learning Outcomes in Complex Mathematics Materials - Hafidhoh, Rodiyatul; Santosa, Cecep Anwar Hadi Firdos; Mutaqin, Anwar (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2026)
This study aimed to examine the effect of the worked-example strategy on students’ learning outcomes in complex mathematics across three time points (pre-test, post-test, delayed-test), and to analyze whether this effect differed based on students’ gender and initial ability levels. A quantitative one-group within-subjects quasi-experimental design was used with 31 eighth-grade students from SMPN 1 Pulosari. Data were collected through validated and reliable test instruments and analyzed using Rasch modeling and inferential statistics. Results showed that the strategy significantly improved learning outcomes (p<0.05), particularly from pre-test to post-test. Although delayed-test scores slightly declined, performance remained high. Moreover, initial differences based on ability levels were observed in the pre-test but they were no longer significant (p>0.05) in the post-test and delayed-test results, suggesting that the strategy helped lower-ability students catch up, reducing learning gaps. Additionally, the study found no significant differences in learning outcomes based on gender (p > 0.05), nor any interaction between gender or ability level and the effectiveness of the worked-example strategy (p>0.05). This study demonstrates the worked example strategy’s effectiveness across time, abilities, and genders in reducing cognitive load and strengthening students’ conceptual understanding. Future studies may compare types, involve varied levels, and use more rigorous designs.